Disulfiram as a potent metallo-β-lactamase inhibitor with dual functional mechanisms - Chen, Cheng; Yang, Ke-Wu; Wu, Lin-Yu; Li, Jia-Qi; Sun, Le-Yun (Chemical communications (Cambridge, England), 2020)
We report a promising NDM-1 inhibitor, disulfiram, which can covalently bind to NDM-1 by forming an S-S bond with the Cys208 residue. Its copper-containing metabolite in vivo , Cu(DTC) 2 , also inactivated NDM-1 through oxidizing the Zn( ii ) thiolate site of the enzyme, therefore exhibiting dual functional inhibitory potential against B1 and B2 subclass MβLs. We report a promising NDM-1 inhibitor, disulfiram, which can covalently bind to NDM-1 by forming an S-S bond with the Cys208 residue. Cu(DTC) 2 also inactivated NDM-1 through oxidizing the Zn( ii ) thiolate site of the enzyme.